EFEKTIVITAS PELAKSANAAN PERATURAN GUBERNUR NOMOR 41 TAHUN 2010 TENTANG STANDARISASI PENGELOLAAN DAYA TARIK WISATA TANPA BERDASARKAN PERATURAN DAERAH - Indra Saputra, I G N Agung Bagus; Putrawan, Suatra (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013)
Published legal product in the hope of being a reference and can be effectivelyimplemented by the community. In this paper will be reviewed implementation of BaliGovernor Rule Number 41 Year 2010 on the Standardization Management TravelAttractions set without the Regional Regulation. There are concerns that if the effectiveimplementation of the Bali Governor Regulation No. 41 of 2010 is given by stipulationwithout regulation as a force that can impose sanctions implementation because itcontains when it is not implemented. Writing method used is the juridical empirical.Empirically implementing the Governor Regulation No. 41 of 2010 Bali have not beeneffective, because the Governor Regulation should not include sanctions, which can beused as a means of coercion for the implementation of these regulations. While the lawcan not be referenced load sanction sanction, because the governor is determinedwithout any regulation by local regulations.
Keywords: Effectiveness, Implementation Governor Regulation, Standardization management of TA, Without Under Local Rule